2023
DOI: 10.1038/s44220-023-00018-y
|View full text |Cite
|
Sign up to set email alerts
|

Green space accessibility helps buffer declined mental health during the COVID-19 pandemic: evidence from big data in the United Kingdom

Abstract: Given accumulating evidence that highlights the negative effect of the COVID-19 pandemic on public mental health, we examine green space accessibility as a potential mitigator. Based on mobility data from 2 million mobile phone users within London between January 2019 and December 2020, we found that, after the COVID-19 outbreak and during lockdowns, residential neighbourhoods within 800 m of the nearest green space had a higher proportion of green-space travellers (0.9-1.4 percentage points) compared with oth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…During the Covid-19 pandemic, when governments significantly restricted people’s movement, the value of locally available urban green spaces dramatically increased. For example, a line of studies has demonstrated the positive impacts of urban green spaces on visitors’ physical and mental health and well-being compared to those who did not visit such amenities 35 – 37 . However, it is well-documented that park visitation trends changed significantly in subsequent phases of the Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the Covid-19 pandemic, when governments significantly restricted people’s movement, the value of locally available urban green spaces dramatically increased. For example, a line of studies has demonstrated the positive impacts of urban green spaces on visitors’ physical and mental health and well-being compared to those who did not visit such amenities 35 – 37 . However, it is well-documented that park visitation trends changed significantly in subsequent phases of the Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…After lifting restrictions and launching nationwide mass vaccination programs, park visitation has gradually recovered to the pre-pandemic level 20 . To study changes and fluctuations in park visitation trends, researchers worldwide tended to apply new methods, including analyzing mobile device location data 22 , 23 , 37 , 41 – 43 .…”
Section: Discussionmentioning
confidence: 99%
“…However, this surge in utilisation revealed discernible inequities, particularly concerning access between white and non-white populations and affluent and low-income neighbourhoods, as elucidated by Jay et al ( 2022) [69]. The bulk of these studies predominantly centred on the United States [18,23,70], the United Kingdom [65], and some European countries such as Germany and France [34]. Nevertheless, disparate access to urban parks during the pandemic was also observed in numerous other countries worldwide [12,27,71].…”
Section: Equity and Access To The Parkmentioning
confidence: 95%
“…One study by Geng et al (2021) found that park visitation rates have increased up to 50% in various European and Asian countries such as Italy, Spain, Sweden, Japan, and South Korea. Moreover, England and Canada have experienced a more substantial increase of up to 100% [27,65]. The Google Mobility Report for 2020 supports this trend, showing a 20.2% increase in park visits during the COVID-19 pandemic compared to the pre-pandemic baseline period [66].…”
Section: Change In Perceived Benefits and Park Usementioning
confidence: 97%
See 1 more Smart Citation